2007
DOI: 10.1111/j.1346-8138.2006.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Fas‐mediated upregulation of vascular endothelial growth factor and monocyte chemoattractant protein‐1 expression in cultured dermal fibroblasts: Role in the inflammatory response

Abstract: The Fas-Fas ligand interaction is the most important pathway in starting apoptosis. In addition, several recent reports have emerged documenting non-apoptotic roles for Fas. However, a non-apoptotic role of Fas in dermal fibroblasts remains unknown. The present study investigated whether Fas stimulation not only promotes apoptosis but also stimulates elements of the inflammatory response such as angiogenesis and macrophage infiltration. Fas stimulation was performed by treating cultured human dermal fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As reported, Fas signaling is associated with inflammation by increasing chemokine secretion and chemoattracting inflammatory cells (25,26). VEGF and MCP-1 have been shown to be crucial for MDSC migration (27,28).…”
Section: Pge 2 Derived From the Fas-ligated Lung Cancer Cells Contribmentioning
confidence: 78%
“…As reported, Fas signaling is associated with inflammation by increasing chemokine secretion and chemoattracting inflammatory cells (25,26). VEGF and MCP-1 have been shown to be crucial for MDSC migration (27,28).…”
Section: Pge 2 Derived From the Fas-ligated Lung Cancer Cells Contribmentioning
confidence: 78%
“…Although we could not completely eliminate the possibility that inflammatory cells induce Fas/FasL-mediated hepatocellular apoptosis, we would like to conclude that particularly fratricidal death by Fas-FasL interactions of neighbouring hepatocytes may actively contribute to ALF. Recently, it was shown that Fas ligation not only promotes apoptosis but also stimulates proinflammatory events such as macrophage infiltration and leukocyte recruitment during liver injury [37]. Leukocyte infiltration has been shown to be not only the cause, but also the consequence of hepatocyte apoptosis [38].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…However, the Fas/FasL system is being increasingly recognized for its ability to trigger inflammation [ 29 ]. Numerous studies have demonstrated that activation of Fas signaling in a variety of non-lymphoid cells, including colonic and lung epithelial cells [ 33 , 34 ], hepatocytes [ 35 ], synoviocytes [ 36 ], macrophages [ 20 ], and fibroblasts [ 37 ], can lead to the expression and release of inflammatory factors in vitro and in vivo, in particular, at the early stage of inflammation development. Such factors may, in turn, recruit inflammatory cells, exacerbating the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%